ChemInform Abstract: The Synthesis of Alkaloids Using Transition‐Metal‐Catalyzed Intramolecular Amination Reactions. Issue 17 (28th April 2014) - Ohno, Hiroaki; Chiba, Hiroaki; Inuki, Shinsuke; Oishi, Shinya; Fujii, Nobutaka
Abstract Review: 54 refs.+subrefs.